An Atypical Presentation of Tuberculomas in an Immunocompetent Host. (August 2018) - Venter, Frederick; Heidari, Arash; Galang, Kristine; Viehweg, Macsen
Tuberculomas are an intracranial form of tuberculosis that account for a third of intracranial lesions in endemic areas. If symptomatic, they usually present as meningitis in an immunocompromised host; however, in patients without signs of meningitis, clinical features are essentially indistinguishable from any other space-occupying lesion. We present a case of central nervous system tuberculosis in an immunocompetent host who presented with new-onset seizures.